2009
DOI: 10.1007/s10147-009-0897-0
|View full text |Cite
|
Sign up to set email alerts
|

A case of bilateral pelvic lymph node involvement in stage 1a1 squamous cell carcinoma of cervix and a review of the literature

Abstract: Stage1a1 cervical cancer has been established to define a subset of the disease in patients who may safely be managed more conservatively and who have an excellent prognosis. Recently, however, a number of stage 1a1 cases with lymph node metastasis have been reported. Some of these cases had positive lymphovascular space invasion (LVSI), which some studies have identified as a negative prognostic factor. There is still, however, disagreement between the International Federation of Gynecology and Obstetrics (FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Finally, although the prognosis of patients with superficially invasive squamous carcinoma of the cervix is generally excellent, occasionally even patients with Stage IA1 tumours develop metastatic disease. 8,9 In recent studies that were related mainly to endocervical neoplasia we observed that the infiltrative tumour cells, particularly towards the invasive margin, exhibited reduced expression of E-cadherin and betacatenin. 10,11 It is well-recognized that these adhesion proteins form a functional complex that maintains cohesion and polarity within epithelial cell groups.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, although the prognosis of patients with superficially invasive squamous carcinoma of the cervix is generally excellent, occasionally even patients with Stage IA1 tumours develop metastatic disease. 8,9 In recent studies that were related mainly to endocervical neoplasia we observed that the infiltrative tumour cells, particularly towards the invasive margin, exhibited reduced expression of E-cadherin and betacatenin. 10,11 It is well-recognized that these adhesion proteins form a functional complex that maintains cohesion and polarity within epithelial cell groups.…”
Section: Introductionmentioning
confidence: 91%
“…The presence of invasion, even of limited extent, also implies an alteration in tumour biology or in tumour–host interactions. Finally, although the prognosis of patients with superficially invasive squamous carcinoma of the cervix is generally excellent, occasionally even patients with Stage IA1 tumours develop metastatic disease 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…More recently Yeasmin reported another stage IA1 squamous cell carcinoma with widespread bilateral pelvic lymph node metastases. (Yeasmin et al, 2009) Lee et al (2006) also reported a case of a 63 year old with < 1 mm invasion depth of disease but with supraclavicular lymph node metastasis and Kang et al (2009)reported a case of stage IA1 squamous cervical carcinoma with invasion of less than 1 mm without lymphovascular involvement but with unilateral ovarian metastasis. Young et al (1993) also reported a case of unilateral ovarian Stage IA1 squamous cell carcinoma metastasis in 1993.…”
Section: Discussionmentioning
confidence: 98%
“…Table 1 summarizes the clinical features of patients with lymph node recurrence reported by previous studies [2][3][4][5][6] . We performed a search of the PubMed database for SCC, stage IA1, and lymph node metastasis, excluding adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%